The potential of intercropping of Crotalaria juncea on the reduction of Pb accumulation in Brassica rapa and Phaseolus vulgaris grown on Pb-contaminated soil - Yekti Sri Rahayu; Moch. Dawam Maghfoer; Tatik Wardiyati (Journal of Degraded and Mining Lands Management, 2022)
Many factors cause increasing Pb contamination in soils, including intensive crop production, motor vehicle exhaust gas around agricultural land areas, or irrigation mixed with household. An effort is needed to minimize Pb contamination in soils. This experiment aimed to examine the potential of Crotalaria juncea L. intercropped for minimizing the accumulation of Pb in vegetable crops grown intensively using agrochemicals. The treatments tested were monoculture of Brassica rapa, monoculture of Phaseolus vulgaris, monoculture of C.juncea, intercropping C. juncea with B.rapa, and intercropping C. juncea  with P. vulgaris. Results of the study showed that planting of C. juncea reduced the total dry weight of B.rapa by 33.47% and increased the total dry weight of P. vulgaris by 17.41% compared to monoculture. Intercropping of B rapa or P. vulgaris with C. juncea reduced the total Pb concentration of B. rapa by 45.64%, and that of P. vulgaris by 16.22%. Planting of C. juncea reduced the Pb concentration in B. rapa by 21.23% (Pb 0.89 mg kg-1) and that in P. vulgaris by 76.03% (Pb 0.93 mg    kg-1). Monoculture planting of C.juncea and intercropping of C. juncea with B. rapa or P. vulgaris reduced the concentration of available Pb and total Pb in the soil to not detected value, compared to monoculture planting of B. rapa and P. vulgaris.